Integrating Drama and AI for Teaching Picturebooks in ELT - Li Ding (CLELEjournal, 2024)
With the help of Chris Wormell's picturebook, The Big Ugly Monster and the Little Stone Rabbit, this contribution illustrates how drama can be combined with text-based generative AI tools to benefit young English learners' critical AI literacy development.